2007
DOI: 10.1007/s00464-007-9712-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy without clip or ligature. An experimental study

Abstract: At late course, coagulated stumps did not allow the leakage or burst, unlike ligated stumps. However, coagulation of the stump seemed to contribute more to epithelial healing. This experimental model suggests that the closure of the stump with only bipolar coagulation was a safe and feasible method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…As such, changing repair methods based on cost would not compromise quality of care. Each LA method of repair in this study, and in the cost curve, has been shown to be clinically reliable (staples [7,9,10], clips [11], electrocautery [12], ligatures [13], hand-ties, endo-loops [19,20]). …”
Section: Disposable Cost (Dollars)mentioning
confidence: 88%
See 1 more Smart Citation
“…As such, changing repair methods based on cost would not compromise quality of care. Each LA method of repair in this study, and in the cost curve, has been shown to be clinically reliable (staples [7,9,10], clips [11], electrocautery [12], ligatures [13], hand-ties, endo-loops [19,20]). …”
Section: Disposable Cost (Dollars)mentioning
confidence: 88%
“…There have been several studies evaluating specific laparoscopic methods such as staples [7][8][9][10], clips [11], and electrocautery [12], all of which have confirmed the clinical safety and efficacy of the respective methods. However, there have been few studies conducted comparing various laparoscopic methods with each other [8,13,14], and there has yet to be evidence to suggest a superior laparoscopic method.…”
mentioning
confidence: 99%
“…In a study of 60 patients, Khanna et al (24) reported that the appendix could safely be divided after bipolar coagulation for approximately 90 seconds. Aslan et al (25) stated that bipolar cautery resulted in better epithelial healing than ligation in an experimental study on rats, and they concluded that it was a reliable method based on tests on burst pressure. However, these results on the use of bipolar cautery are not supported by other studies.…”
Section: Cauterization or Vessel Sealing Devicesmentioning
confidence: 99%
“…In the BPC subgroups, the appendectomy was performed with exactly the same technique as in the L; but coagulation with bipolar electrocautery (Valleylab) took 10 seconds, and it was repeated once more because the device lacked a feedback mechanism. Disappearance of the bubbles and formation of a white line, as in the L subgroups, were accepted as complete closure of the stump [2]. The coagulation parameters of the bipolar electrocautery were Fig.…”
Section: Methodsmentioning
confidence: 99%